Level Of Satisfaction Among Graduates - et. al., Ma. Erenita V. Bahian, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to determine the level of satisfaction among graduate students at Eastern Visayas State University-Ormoc Campus in Ormoc City. . About 231 students are selected as samples using convenience sampling. The data is collected by the use of a survey questionnaire and analyzed using SPSS software. The findings reveal that students have a high level of satisfaction on Personal and Professional factors, and a moderate level of satisfaction on Student Support and Instruction-related factors. The younger group of both males and females enrolled in Education and Technology programs has a higher level of satisfaction than the older group enrolled in Engineering, which has a moderate level of satisfaction. There is no significant difference in personal and professional satisfaction levels by gender and age, but there is a significant difference by program. When compared to Technology and Engineering students, Education students are more satisfied. The relationship between variables is found to be moderately significant.